PROTECTION OF CENTRIFUGAL PUMPS FROM ABRASIVE WEAR USING A VACUUM HYDROCYCLONE - Kassymbekov Zhuzbay Kozhabaevich; Atamanova Olga Viktorovna; Alimova Kulyash Kapbasovna; Kassymbekov Galymzhan Zhuzbaevich (Scientific Journal of Pedagogy and Economics, 2020)
The design features of the existing design and technology for the protection of downhole pumps of the ECV type from abrasive wear during operation are considered and analyzed. Based on the analysis, a new method for capturing solid impurities on the suction line of a borehole pump of the ECV type using a pressure-vacuum hydrocyclone is proposed. It is specified that at field tests of a prototype of new installation technological process is estimated on the pressure-expense characteristic and technological-operational indicators according to requirements of GOST 6134-81 " pumps dynamic. Test method. " In this case, the flow rate of the base pump on water is determined by means of a turbine water meter mounted on a water-lifting pipe with a valve. The performance of the hydraulic elevator is established by the volumetric method, and the head in front of the valve of the pump pressure pipe using an approximate pressure gauge. It is established that the flow-pressure characteristics of the base submersible pump ECV are provided in full (water flow 60-70 m3 /h, head - 110-118 m), overload on the electric motor is not detected (ammeter readings are within the permissible limits-68-71 amperes), the degree of water purification is 95-96%. It is noted that the implementation of a flexible packer device with slots and the presence on the surface of the second minihydrocyclone-thickener significantly improves the functioning of the adopted scheme of water treatment. It turned out that with this technology, the overload of the pump motor is reduced by cooling with water without mechanical impurities.